The Effectiveness of Moringa Leaf and Tuna Fish Oil Biscuits in Advancing Hemoglobin Levels and Breast Milk Volume - Kurnia Dewiani; Riana Versita ; Fitri Ramadhaniati ; Endah Purda Listya (The Indonesian Institute of Science and Technology Research, 2025)
Anemia in breastfeeding mothers during the postpartum period can reduce breast milk production and affect its nutritional quality. An innovative food supplement in the form of moringa leaf biscuits combined with tuna fish oil offers a convenient option with strong macro- and micronutrient profiles that may improve hemoglobin levels and breast milk volume. This study aimed to evaluate the effectiveness of Moringa Leaf Biscuits and Tuna Fish Oil on hemoglobin levels and breast milk volume in postpartum women. Using a quasi-experimental design with a pretest–posttest and control group, 50 respondents from four community health centers were randomly assigned to either an intervention group (30 respondents) or a control group (20 respondents). The biscuits were administered for 14 days, twice daily. The findings revealed a significant increase in hemoglobin levels in the intervention group after biscuit consumption, while the control group showed no meaningful change. The intervention group experienced an average increase of 14.03%, compared with only 1.21% in the control group. Breast milk volume measurements also demonstrated a significant improvement, with the intervention group showing an increase of 64.8% compared with the control group, whose increase averaged only 4.5%. These results indicate that moringa leaf biscuits combined with tuna fish oil effectively enhance hemoglobin levels and breast milk volume in postpartum mothers.